The Effect of Managerial Ownership, Financial Performance, Corporate Competition on Stock Prices with Capital Structure as the Intervening Variable in the Coal Mining Companies Listed on the Indonesia Stock Exchange - Yulia Afriani; Abdul Rakhman Laba; Andi Aswan (Magister Management, Hasanuddin University, 2020)
This study aimed to find out the effect of managerial ownership, financial performance, corporate competition on stock prices with capital structure as the intervening variable in the coal mining companies listed on the Indonesia Stock Exchange. Managerial ownership variables by the shareholding presentation. Financial performance variables by Total Asset Turnover (TATO). Firm competition variable by Concentration Ratio (CR). Capital structure variables by Debt to Equity Ratio (DER). Stock prices variable by Price to Book Value (PBV). The population of this study was the coal mining companies listed on the IDX. This study used Purposive as the sampling technique. The data source was secondary data from financial statements published through the IDX official website. This study used descriptive statistics and inferential statistics with a quantitative approach using regression techniques with the E-Views version 10 program. The results of this study showed that the dealings of managerial ownership had a positive and significant effect on DER, TATO had a negative and not significant effect on DER, while CR had a negative and significant effect on DER. The dealings of managerial ownership, TATO, DER has a positive and significant effect on PBV, while CR has a negative and not significant. The dealings of managerial ownership influences PBV through DER, interestingly TATO has no effect on PBV through DER and CR influences PBV through DER